Corporate Mining Offences: Assessing The Interpretation of Ultimum Remedium - Lestari, Ida Ayu Sridiah; Satria, Hariman (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The principle of ultimum remedium in criminal law is more accurately referred to as a moral principle for legislators (legislative ethics) so that they can think about whether or not an act needs to be criminalized, including the threat of criminal sanctions. Normatively, in Indonesian criminal law the principle of ultimum remedium is strictly regulated in Article 100 and the general explanation of point 5 of the PPLH Law. In the Minerba Law, the principle of ultimum remedium is not normative. In decision Number 46/Pid.B/LH/2021/PT Kdi, it is implied that a corporate crime occurred by the defendant PT Bososi Pratama. The panel of judges acquitted the defendant PT Bososi Pratama by interpreting the principle of ultimum remedium. This interpretation emerged because the position of criminal sanctions in the Mineral and Coal Law is still unclear, whether as ultimum remedium or primum remedium.